2019
DOI: 10.3847/1538-4357/ab2392
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Dark Matter Imprint on Low-mass Main-sequence Stars in the Milky Way Nuclear Star Cluster

Abstract: In this work, we study the impact of asymmetric dark matter (ADM) on low-mass main-sequence stars in the Milky way's nuclear star cluster, where the dark matter (DM) density is expected to be orders of magnitude above what is found near the Sun (ρ DM 10 3 GeV cm −3 ). Using a modified stellar evolution code and considering a DM particle (m χ = 4 GeV) with a spin-dependent interaction cross section close to the limits allowed by direct detection, we found that the interactions of ADM with baryons in the star's … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Such type of DM is usually called asymmetric dark matter (ADM).There is a large number of articles that have explored ADM in different astrophysical contexts. Examples are the studies of ADM in the Sun [13][14][15][16] and other stars [17,18]. This DM type is the subject of our study in this letter.…”
Section: Introductionmentioning
confidence: 91%
“…Such type of DM is usually called asymmetric dark matter (ADM).There is a large number of articles that have explored ADM in different astrophysical contexts. Examples are the studies of ADM in the Sun [13][14][15][16] and other stars [17,18]. This DM type is the subject of our study in this letter.…”
Section: Introductionmentioning
confidence: 91%
“…Ongoing studies have been focusing on different aspects of compact objects, including bosonic DM stars (Eby et al 2016;Lee et al 2021, in preparation), formation of neutron stars through the accretioninduced collapse of DM-admixed white dwarfs (WDs; Leung et al 2019;Zha et al 2019), tidal properties of DM-admixed neutron stars (Leung et al 2021, in preparation), thermalization of the WD core to produce a thermonuclear runaway (Bramante 2015;Acevedo & Bramante 2019;Janish et al 2019;Steigerwald et al 2019), and thermonuclear supernovae with point-mass DM cores (Leung et al 2015a). Other than compact objects, effects of DM admixture on stellar formation (Arun et al 2019) and evolution (Scott et al 2008;Freese et al 2016;Lopes & Lopes 2019) are actively investigated. In particular, the evolution of AGB stars is used to constrain the properties of axion-like particles (Dolan et al 2021).…”
Section: Dm-admixed Stellar Objectsmentioning
confidence: 99%
“…There may exist DM stars (DMSs) [48,49] powered by WIMP DM annihilation [50,51]. In regions of high DM density, such as the Galactic center, the capture and annihilation of WIMP DM by stars has the potential to significantly alter their evolution [52][53][54][55]. In Reference [56] it was shown that WIMPs accreted onto neutron stars may provide a mechanism to seed strangelets in compact objects for WIMP masses above a few GeV.…”
Section: Introductionmentioning
confidence: 99%